Compared implementations of PDM systems based on UML specifications. (13th September 2005) - Merlo, Christophe; Eynard, Benoit; Girard, Philippe; Odinot, Aurelien, Thomas Gallet
With regard to product development processes, the PDM (Product Data Management) system aims at the management of product data and related documents. The specification and implementation of such a system strongly depends on company needs and also on the system characteristics. Generally, the PDM system requires a specific way of structuring product data and its management. In recent works, the use of the UML approach has been proposed to formalise the specifications in order to enable the implementation of a PDM system. The main goal of this paper is to study the implementation of such UML based specifications through two different PDM systems, in order to assess their functionalities according to the needs of product development process management. The case study used is extracted from a turboprop aircraft project.